Penggunaan Asbuton (Ac-Wc) Pracampur Pada Proyek Preservasi Jalan Duri – Kandis - Sp. Palas - Siak II (Pekanbaru) (E-Katalog) - Islah , Mhd.; Adeswastoto, Hanantatur (Journal of Engineering Science and Technology Management (JES-TM), 2023)
Asbuton is natural asphalt whose use in Indonesia is no stranger. One of the asbuton technologies that has been widely used is pre-mixed asbuton. Pre-mixed asphalt is one type of modified asphalt used in Indonesia. Pre-mixed Asphalt is processed and mixed with Pen 60/70 Asphalt at a factory that meets certain requirements, so that it is equivalent to Modified Asphalt. Premixed Asbuton products have a minimum level of purity of 90%, so they still contain a maximum of 10% fine minerals. This type of processed Pre-mixed Asphalt is the mobile container circulates directly inside the Asphalt Mixing Plant (AMP) boiler without the addition of Asphalt Pen 60/70 to produce Hot Mix Asphalt (Hotmix) which is equivalent to using Modified Asphalt. From the results of testing in the laboratory it was found that the asphalt mixture using pre-mixed asphalt has better technical properties than the conventional asphalt mixture (made using Pen 60/70 asphalt)